HUMAN RIGHTS VIOLATIONS AGAINST SEVERELY ILL VOTERS IN GENERAL ELECTIONS: A SIYASAH DUSTURIYAH PERSPECTIVE - Abd. Razak; Wahyuni; Mohamad Oktafian (Qaumiyyah: Jurnal Hukum Tata Negara, 2026)
Voting rights in general elections constitute a fundamental human right guaranteed by the constitution and serve as an essential element in realizing an inclusive democracy. However, in practice, several issues remain, particularly concerning the fulfillment of voting rights for vulnerable groups, including voters who are in severe medical conditions. Critcally ill voters are considered vulnerable because the exercise of their political rights may conflict with their rights to health, safety, freedom of will, and respect for human dignity. This study aimed to examine the potential human rights violations in the implementation of voting rights for severely ill voters in the 2024 General Election in Tomini Utara Village, Parigi Moutong Regency, and to analyze the issue from the perspective of Siyasah Dusturiyah. This research employed an empirical juridical method using statutory and case approaches. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the 2024 General Election in Tomini Utara Village still has the potential to create human rights violations against severely ill voters, particularly when voters who are medically unable to express their political will freely are still directed to exercise their voting rights. Such conditions potentially violate the principles of direct, free, and secret voting while also neglecting the rights to health and human dignity. From the perspective of Siyasah Dusturiyah, this situation demonstrates the need to strengthen policies and technical guidelines that are more oriented toward humanitarian values. Abstrak Pelaksanaan hak pilih oleh pemilih sakit berat dalam Pemilihan Umum berpotensi menimbulkan pelanggaran hak asasi manusia, khususnya terhadap hak kesehatan, kebebasan berkehendak dan martabat kemanusiaan. Penelitian ini bertujuan untuk mengkaji potensi pelanggaran hak asasi manusia dalam pelaksanaan hak pilih oleh pemilih sakit berat pada Pemilihan Umum Tahun 2024 di Desa Tomini Utara Kabupaten Parigi Moutong serta menelaahnya dari perspektif Siyasah Dusturiyah. Metode penelitian yang digunakan adalah penelitian yuridis empiris dengan pendekatan perundang-undangan dan pendekatan kasus. Pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa pelaksanaan Pemilihan Umum Tahun 2024 di Desa Tomini Utara berpotensi menimbulkan pelanggaran hak asasi manusia terhadap dua pemilih sakit berat yang dimana secara medis tidak mampu menyatakan kehendak politik secara bebas namun tetap diarahkan untuk menggunakan hak pilihnya. Pelaksanaan hak pilih oleh pemilih sakit berat dalam Pemilihan Umum dapat menimbulkan pelanggaran hak asasi manusia apabila dilakukan dalam kondisi yang memperburuk kondisi kesehatan pemilih akibat tidak didasarkan pada kesadaran penuh atau mengabaikan kehendak bebas pemilih. Ketidakmampuan Dalam perspektif Siyasah Dusturiyah, kondisi tersebut menunjukkan perlunya penguatan kebijakan dan pedoman teknis yang lebih berorientasi pada nilai kemanusiaan khususnya kategori bagi pemilih sakit berat.